1986
DOI: 10.7326/0003-4819-105-6-947
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Deficiency Hypothesis of Hypertension: A Critique

Abstract: Primary (essential) hypertension has recently been related to calcium deficiency, rather than excess. The evidence used to support this hypothesis includes surveys showing lesser dietary intake of calcium, lower levels of ionized calcium in the blood, and reduction of blood pressure with calcium supplements. This critique examines each of these points and the theoretical construct used to explain the hypothesis. We conclude that the theoretical construct is based on the use of only a portion of available exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…21 In genetically hypertensive rats, calcium supplementation during the developmental phase of hypertension diminished the blood pressure increase. 22 In another study, however, genetically hypertensive rats fed a calcium-deficient diet did not show an increased blood pressure rise compared with rats fed a normal diet.…”
mentioning
confidence: 99%
“…21 In genetically hypertensive rats, calcium supplementation during the developmental phase of hypertension diminished the blood pressure increase. 22 In another study, however, genetically hypertensive rats fed a calcium-deficient diet did not show an increased blood pressure rise compared with rats fed a normal diet.…”
mentioning
confidence: 99%
“…Even though total extracellular calcium levels, as measured in serum, tend to be higher in people with hypertension [7], it is unlikely that such slightly elevated levels could break through the normal protective mechanisms which maintain the usual 1,000-fold or greater differential between extracellular and intracellular calcium concentrations. Even though total extracellular calcium levels, as measured in serum, tend to be higher in people with hypertension [7], it is unlikely that such slightly elevated levels could break through the normal protective mechanisms which maintain the usual 1,000-fold or greater differential between extracellular and intracellular calcium concentrations.…”
Section: Possible Mechanismsmentioning
confidence: 98%
“…Kesteloot et al (1983) reported a negative and highly significant correlation between serum total calcium and 24-hr urinary sodium excretion in their epidemiological study. Moreover, Kaplan and Meese (1986) have suggested that the exaggerated natriuresis in hypertensives probably increases urinary calcium excretion and somewhat lowers the level of circulating calcium. Because it has been demonstrated (Richards et al 1985;Weidmann et al 1986) that urinary calcium output is increased by ANP infusion in normal volunteers, our finding of a significant inverse correlation between plasma ANP and serum calcium suggest that the increased ANP level in hypertensives may not only suppress PRA, but may also increase urinary calcium output and lower the serum level of calcium.…”
Section: Discussionmentioning
confidence: 99%